Quality control in SARS-CoV-2 RBD-Fc vaccine production using LC–MS to confirm strain selection and detect contaminations from other strains - Pipob Suwanchaikasem; Kaewta Rattanapisit; Richard Strasser; Waranyoo Phoolcharoen (Scientific Reports, 2024)
Abstract Coronavirus disease of 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is an ongoing outbreak, disrupting human life worldwide. Vaccine development was prioritized to obtain a biological substance for combating the viral pathogen and lessening disease severity. In vaccine production, biological origin and relevant materials must be carefully examined for potential contaminants in conformity with good manufacturing practice. Due to fast mutation, several SARS-CoV-2 variants and sublineages have been identified. Currently, most of COVID-19 vaccines are developed based on the protein sequence of the Wuhan wild type strain. New vaccines specific for emerging SARS-CoV-2 strains are continuously needed to tackle the incessant evolution of the virus. Therefore, in vaccine development and production, a reliable method to identify the nature of subunit vaccines is required to avoid cross-contamination. In this study, liquid chromatography-mass spectrometry using quadrupole-time of flight along with tryptic digestion was developed for distinguishing protein materials derived from different SARS-CoV-2 strains. After analyzing the recombinantly produced receptor-binding domain (RBD) of the SARS-CoV-2 spike protein, nine characteristic peptides were identified with acceptable limits of detection. They can be used together to distinguish 14 SARS-CoV-2 strains, except Kappa and Epsilon. Plant-produced RBD-Fc protein derived from Omicron strains can be easily distinguished from the others with 4–5 unique peptides. Eventually, a peptide key was developed based on the nine peptides, offering a prompt and precise flowchart to facilitate SARS-CoV-2 strain identification in COVID-19 vaccine manufacturing.